Edukasi dan Pelatihan Tanaman Obat Keluarga di Kelurahan Sri Meranti, Pekanbaru - Rahmat Azhari Kemal; Arfianti Arfianti; Ulfah Ulfah; Bayu Fajar Pratama (Jurnal Surya Masyarakat, 2023)
A family medicinal plant is a group of plants that have health benefits for family health. However, its utilization should be increased. During the COVID-19 pandemic, public interest in traditional herbal medicine increases. Therefore, it has to be balanced with increased knowledge of family medicinal plants as well as knowledge of good practices in the utilization and care of the plants. Education and training of family medicinal plants were conducted for representatives of Sri Meranti District, Pekanbaru City, Riau. Education on types of family medicinal plants and how to properly utilize them was delivered online via the Zoom Meeting platform. The education was followed by training on how to plant and care for the family's medicinal plants. Participants were also given seedlings of family medicinal plants for their yards. After the education, participants’ knowledge of how to utilize family medicinal plants increased. With the increased knowledge as well as the seedlings provided, people in the Sri Meranti district are expected to cultivate and utilize family medicinal plants properly.